Second harmonic imaging: a new ultrasound technique to assess human brain tumour perfusion. Issue 3 (1st March 2003) - Harrer, J U; Mayfrank, L; Mull, M; Klötzsch, C
Abstract : Background: Second harmonic imaging is a new ultrasound technique that allows evaluation of brain tissue perfusion after application of an ultrasound contrast agent. Objective: To evaluate the potential of this technique for the assessment of abnormal echo contrast characteristics of different brain tumours. Methods: 27 patients with brain tumours were studied. These were divided into four groups: gliomas, WHO grade III–IV (n = 6); meningiomas (n = 9); metastases (n = 5); and others (n = 7). Patients were examined by second harmonic imaging in a transverse axial insonation plane using the transtemporal approach. Following intravenous administration of 4 g (400 mg/ml) of a galactose based echo contrast agent, 62 time triggered images (one image per 2.5 seconds) were recorded and analysed off-line. Time–intensity curves of two regions of interest (tumour tissue and healthy brain tissue), including peak intensity (PI) (dB), time to peak intensity (TP) (s), and positive gradient (PG) (dB/s), as well as ratios of the peak intensities of the two regions of interest, were derived from the data and compared intraindividually and interindividually. Results: After administration of the contrast agent a marked enhancement of echo contrast was visible in the tumour tissue in all patients. Mean PI and PG were significantly higher in tumour tissue than in healthy brain parenchyma (11.8 v 5.1 dB and 0.69 v 0.16 dB/s; p < 0.001). TP did not differ significantly (37.1 v 50.2 s; p = 0.14). A tendency towards higher PI and PG as well as shorter TP was apparent in malignant gliomas. When comparing different tumour types, however, none of these variables reached significance, nor were there significant differences between malignant and benign tumours in general. Conclusions: Second harmonic imaging not only allows identification of brain tumours, but may also help in distinguishing between different tumour types. It gives additional and alternative information about tumour perfusion. Further studies are needed to evaluate the clinical potential of this technique in investigating brain tumours—for example in follow up investigations of patients undergoing radiation or chemotherapy—especially in comparison with neuroradiological and neuropathological findings.